2014
DOI: 10.1161/jaha.114.000968
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute‐2 Promotes miR‐18a Entry in Human Brain Endothelial Cells

Abstract: BackgroundCerebral arteriovenous malformation (AVM) is a vascular disease exhibiting abnormal blood vessel morphology and function. miR‐18a ameliorates the abnormal characteristics of AVM‐derived brain endothelial cells (AVM‐BEC) without the use of transfection reagents. Hence, our aim was to identify the mechanisms by which miR‐18a is internalized by AVM‐BEC. Since AVM‐BEC overexpress RNA‐binding protein Argonaute‐2 (Ago‐2) we explored the clinical potential of Ago‐2 as a systemic miRNA carrier.Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…D: ChIP PCR was conducted with the resulting precipitated DNA. miR-18a was expressed in AVM-derived brain ECs and that Ago-2 facilitated miR-18a entry into brain ECs and affected vascular formation in patients of cerebral arteriovenous malformation (Dews et al, 2006;Ferreira et al, 2014). The overexpression of miR-18a significantly inhibited three-dimensional spheroid sprouting in vitro (Doebele et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D: ChIP PCR was conducted with the resulting precipitated DNA. miR-18a was expressed in AVM-derived brain ECs and that Ago-2 facilitated miR-18a entry into brain ECs and affected vascular formation in patients of cerebral arteriovenous malformation (Dews et al, 2006;Ferreira et al, 2014). The overexpression of miR-18a significantly inhibited three-dimensional spheroid sprouting in vitro (Doebele et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…miR-18a, as an important member of the miR-17-92 cluster, has certain impacts on angiogenesis, tumor invasion, and metastasis in gastric cancer and hepatocellular carcinoma Wu et al, 2013). Ferreira et al (2014) showed that miR-18a was expressed in cerebral vascular endothelium and that Ago-2 could promote miR-18a entry in brain endothelial cells (ECs) and angiogenesis in cerebral arteriovenous malformation (Dews et al, 2006). However, whether miR-18a was involved in regulating the function of glioma vascular endothelial cells (GECs) as well as permeability of the blood-tumor barrier (BTB) still remained unclear.…”
Section: Keymentioning
confidence: 99%
“…Non-vesicle associated miRNAs are also transferred to recipient cells and affect gene expression [12,13,47]. Effects of HDL/miRNA uptake by recipient cells have been noted [12,13], and Ago2-associated miR-18a from diseased brain endothelial H. Iftikhar and G. E. Carney Prospects & Overviews .... cells is internalized by non-diseased brain endothelial cells but not by other cell types tested [47].…”
Section: Is There Evidence For Functionality Of Uptaken Mirnas In Recmentioning
confidence: 99%
“…The strategies that researchers used to deliver miRNAs in vivo varied and included injections of vesicles, miRNAs or antagomirs into the bloodstream or specific tissues; in other studies cells expressing miRNAs were injected or vesicles were implanted directly into tissues [32,38,47,61,[74][75][76]. In many cases it is not clear from these experiments how the amount of exogenously supplied miRNA compares to the amount present in normal or diseased animals.…”
Section: Mirnas Are Taken Up and Alter Recipient Cell Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation